Expanding ACTA2 genotypes with corresponding phenotypes overlapping with smooth muscle dysfunction syndrome. Issue 8 (14th May 2022) - Kaw, Anita; Kaw, Kaveeta; Hostetler, Ellen M.; Beleza‐Meireles, Ana; Smith‐Collins, Adam; Armstrong, Catherine; Scurr, Ingrid; Cotts, Timothy; Aatre, Rajani; Bamshad, Michael J.; Earl, Dawn; Groner, Abraham; et al.
Abstract: Pathogenic variants in ACTA2, encoding smooth muscle α‐actin, predispose to thoracic aortic aneurysms and dissections. ACTA2 variants altering arginine 179 predispose to a more severe, multisystemic disease termed smooth muscle dysfunction syndrome (SMDS; OMIM 613834). Vascular complications of SMDS include patent ductus arteriosus (PDA) or aortopulmonary window, early‐onset thoracic aortic disease (TAD), moyamoya‐like cerebrovascular disease, and primary pulmonary hypertension. Patients also have dysfunction of other smooth muscle‐dependent systems, including congenital mydriasis, hypotonic bladder, and gut hypoperistalsis. Here,  we describe five patients with novel heterozygous ACTA2 missense variants,  p.Arg179Gly, p.Met46Arg, p.Thr204Ile, p.Arg39Cys, and p.Ile66Asn, who have clinical complications that align or overlap with SMDS. Patients with the ACTA2 p.Arg179Gly and p.Thr204Ile variants display classic features of SMDS. The patient with the ACTA2 p.Met46Arg variant exhibits exclusively vascular complications of SMDS, including early‐onset TAD, PDA, and moyamoya‐like cerebrovascular disease. The patient with the ACTA2 p.Ile66Asn variant has an unusual vascular complication, a large fusiform internal carotid artery aneurysm. The patient with the ACTA2 p.Arg39Cys variant has pulmonary, gastrointestinal, and genitourinary complications of SMDS but no vascular manifestations. Identifying pathogenic ACTA2 variants associated with features of SMDS is critical for aggressive surveillance and management of vascular and nonvascular complications and delineating the molecular pathogenesis of SMDS.